2021
DOI: 10.1042/ebc20200143
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary acquisition and mode of functions of promoter-associated non-coding RNAs (pancRNAs) for mammalian development

Abstract: Increasing evidence has shown that many long non-coding RNAs (lncRNAs) are involved in gene regulation in a variety of ways such as transcriptional, post-transcriptional and epigenetic regulation. Promoter-associated non-coding RNAs (pancRNAs), which are categorized into the most abundant single-copy lncRNA biotype, play vital regulatory roles in finely tuning cellular specification at the epigenomic level. In short, pancRNAs can directly or indirectly regulate downstream genes to participate in the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Before being translated into protein, pre-mRNA is specially spliced in the nucleus to generate mature mRNA, which is subsequently translocated from the heart to the ribosome in the cytoplasm. Only when the structural gene ultimately succeeds in producing an active protein is the gene considered functional ( 60 ). Several studies have demonstrated that lncRNAs can control mRNA translation in various ways ( 61 ).…”
Section: Overview Of Lncrnamentioning
confidence: 99%
“…Before being translated into protein, pre-mRNA is specially spliced in the nucleus to generate mature mRNA, which is subsequently translocated from the heart to the ribosome in the cytoplasm. Only when the structural gene ultimately succeeds in producing an active protein is the gene considered functional ( 60 ). Several studies have demonstrated that lncRNAs can control mRNA translation in various ways ( 61 ).…”
Section: Overview Of Lncrnamentioning
confidence: 99%
“…The potential involvement of human-specific noncoding RNAs to achieve human-biased expression of conserved genes Our previous research demonstrated that the presence of high GC content in the promoter tends to generate divergent lncRNAs upstream of genes in a head-tohead manner (referred to as pancRNAs) [32,58,59]. pancRNAs have the ability to participate in various biological processes through specifically up-regulating the partner mRNAs [58].…”
Section: Connection Of Tmem25-triggered Pathway With the Network Of H...mentioning
confidence: 99%
“…In addition to the roles played by transcribed lncRNA molecules, several studies have suggested the importance of cis -acting RNA polymerase II-transcribing nascent lncRNAs in the regulation of neighboring genes through their effects on histone modifications [ 101 , 102 ]. The lnc RNAs expressed from gene promoter region are referred to as promoter-associated lncRNA, which are categorized into most abundant ncRNA, and play pivotal roles in the regulation of downstream genes [ 103 ].…”
Section: Induction Of Meiotic Dsb Via the Expression Of Long Ncrnamentioning
confidence: 99%